2005
DOI: 10.17705/1cais.01504
|View full text |Cite
|
Sign up to set email alerts
|

Flow in Computer-Mediated Environments: Promises and Challenges

Abstract: This paper provides a critical review to analyze the promises and important challenges of studying flow, a psychological state, in the computer-mediated environments (CME). Despite the strong interest in IS, HCI, Marketing, Education, and other research disciplines over more than a decade, adapting the phenomenon of flow to computer users shows high inconsistencies and discrepancies in the literature. In addition, few studies attempt to provide a coherent picture of the area. Based on a careful examination of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
137
0
5

Year Published

2007
2007
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(145 citation statements)
references
References 43 publications
3
137
0
5
Order By: Relevance
“…The literature is inconclusive about which measurement is more accurate or correct (Finneran and Zhang 2005). By establishing the effect for both measurements our findings have been demonstrated to be robust.…”
Section: Summary and Concluding Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…The literature is inconclusive about which measurement is more accurate or correct (Finneran and Zhang 2005). By establishing the effect for both measurements our findings have been demonstrated to be robust.…”
Section: Summary and Concluding Discussionmentioning
confidence: 55%
“…The second variation measures the overall flow directly by providing a description of online flow and asking respondents to rate the online flow they experienced while using the internet or a specific web site (Novak, Hoffman, and Yung 2000). The literature is inconclusive about which measurement is more accurate or correct (Finneran and Zhang 2005). Therefore, we used the indirect variation in Study 1 and we used both variations in Study 2.…”
Section: General Methodsmentioning
confidence: 99%
“…One experiences higher engagement when his or her skills and the perceived challenge are high and in balance [34,49,87,121]). MVAS with technology excellence could appropriately adjust the challenge experienced to fit user skills through properly designed interface, effective customer feedback, and reliable backend systems.…”
Section: Hypotheses Developmentmentioning
confidence: 99%
“…Employees who experience more playfulness are more likely to sustain their participation with the information system (Davis & Wong, 2007). Finneran and Zhang (2005) argued that a computer-mediated environment conducive to flow would result in positive attitudes and outcomes for an individual. Davis et al (1992) found that playfulness is one of the key drivers of behavioral intention to use computers.…”
Section: The Influence Of Playfulness On Perceived Ease Of Use Attitmentioning
confidence: 99%